Digital Revolution in Islamic Education: Building the Branding of Religious Schools in Rural Indonesia through Innovative Digital Marketing Strategies - Adimas Rizqon; Aufa Fimaisarah (Universitas Nurul Jadid, 2024)
This research focuses on the implementation of digital marketing strategies in educational institutions, with a case study at SMP NU Darul Falah Masaran, Sragen. The purpose of this study is to analyze the effectiveness of the implementation of digital marketing in increasing the visibility and attractiveness of schools in the digital era. The research method used is qualitative research with a descriptive approach, where data is collected through in-depth interviews, participatory observations, and documentation studies. Data analysis was carried out using the Miles and Huberman interactive analysis model which included data reduction, data presentation, and conclusion drawn/verification. The results of the study show that careful planning, structured organization, and continuous evaluation play an important role in the success of the digital marketing strategy implemented. The implications of this study show that educational institutions can increase the effectiveness of their promotions by utilizing digital marketing in a more responsive and adaptive manner to changes in digital trends. This research makes a significant contribution to the development of educational marketing strategies in the digital era, especially in the context of secondary education